Associations among Periodontitis, Calcified Carotid Artery Atheromas, and Risk of Myocardial Infarction. (January 2020) - Gustafsson, N.; Ahlqvist, J.; Näslund, U.; Buhlin, K.; Gustafsson, A.; Kjellström, B.; Klinge, B.; Rydén, L.; Levring Jäghagen, E.
Cardiovascular disease is a common cause of morbidity and premature mortality. Cardiovascular disease can be prevented when risk factors are identified early. Calcified carotid artery atheromas (CCAAs), detected in panoramic radiographs, and periodontitis have both been associated with increased risk of cardiovascular disease. This case-control study aimed to 1) investigate associations between periodontitis and CCAA detected in panoramic radiographs and 2) determine the risk of future myocardial infarctions due to CCAA combined with periodontitis. We evaluated 1, 482 participants (738 cases and 744 controls) with periodontitis and CCAAs recruited from the PAROKRANK study (Periodontitis and Its Relation to Coronary Artery Disease). Participants were examined with panoramic radiographs, including the carotid regions. Associations between myocardial infarction and periodontitis combined with CCAA were evaluated in 696 cases and 696 age-, sex-, and residential area–matched controls. Periodontitis was evaluated radiographically (as degree of bone loss) and with a clinical periodontal disease index score (from clinical and radiographic assessments). We found associations between CCAA and clinical periodontal disease index score among cases (odds ratio [OR], 1.51; 95% CI, 1.09 to 2.10; P = 0.02) and controls (OR, 1.70; 95% CI, 1.22 to 2.38; P < 0.01), although not between CCAA and the degree of bone loss. In a multivariable model, myocardial infarction was associated with CCAA combined with periodontitis, as assessed by degree of bone loss (OR, 1.75; 95% CI, 1.11 to 2.74; P = 0.01). When the cohort was stratified by sex, only men showed a significant association between myocardial infarction and CCAA combined with periodontitis. Participants with clinically diagnosed periodontitis exhibited CCAA in panoramic radiographs more often than those without periodontitis, irrespective of the presence of a recent myocardial infarction. Participants with combined periodontitis and CCAA had a higher risk of having had myocardial infarction as compared with participants with either condition alone. These findings implied that patients in dental care might benefit from dentists assessing panoramic radiographs for CCAA—particularly, patients with periodontitis who have not received any preventive measures for cardiovascular disease.